Pengaruh Motivasi, Kemampuan, Komitmen, Lingkungan Terhadap Kinerja Pegawai (Studi Kasus pada Pegawai PT. PLN Unit Layanan Transmisi Gardu Induk (ULTG) Malang) - Angga Riduansyah Adi Pranata; Rois Arifin; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThe existence of human resources is an important aspect in the organization, because it will determine the effectiveness of the organization. Increasing an individual's ability has the potential to improve group performance and improving the performance of all employees will improve organizational performance which will contribute to accelerating achievements and goals set by the organization. This research is an analytical survey research that aims to test and analyze the influence of motivation, ability, commitment, environment simultaneously or partially on employee performance (Case Study on Employees of PT. PLN Transmission Service Unit Substation (ULTG) Malang). The population in the study were employees of PT PLN Malang Substation Transmission Service Unit (ULTG) amounted to 37 people with saturated sampling technique or total sampling The data analysis method used in this study is multiple linear regression, F test and T test. The results of this study prove statistically that motivation, ability, commitment, environment simultaneously or partially affect employe performance (Case Study on Employees of PT PLN Transmission Service Unit Substation (ULTG) Malang). So that the proposed hypothesis is proven and accepted. Keywords: Motivation, Ability, Comment, Environment, Performance